2001
DOI: 10.21829/abm54.2001.868
|View full text |Cite
|
Sign up to set email alerts
|

Análisis florístico de dos áreas con bosque mesófilo de montaña en el estado de Hidalgo, México: Eloxochitlán y Tlahuelompa

Abstract: Los bosques mesófilos de Eloxochitlán y Tlahuelompa, enclavados en la Sierra Madre Oriental y en la Huasteca Hidalguense, representan dos manchones con diferente composición florística en el estado de Hidalgo. Estos bosques en general presentan tres estratos arbóreos: uno alto (20-30 m y hasta 40 m), uno medio (8-20 m) y uno bajo (2-8 m). Se ofrece una lista de plantas vasculares de ambos sitios constituida por 394 especies, 266 géneros y 110 familias. Al realizar un análisis de la distribución actual de los g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
15

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 12 publications
2
9
0
15
Order By: Relevance
“…At the community level, the richness of woody species at the three study sites was similar to that reported by Williams-Linera et al (2003) for other beech forests in Mexico and also similar to those recorded in other studies of montane cloud forest in Hidalgo and the state of Mexico (Alcántara & Luna-Vega 2001, Williams-Linera et al 2003. Moreover, the RIV estimates showed that Fagus grandifolia subsp.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…At the community level, the richness of woody species at the three study sites was similar to that reported by Williams-Linera et al (2003) for other beech forests in Mexico and also similar to those recorded in other studies of montane cloud forest in Hidalgo and the state of Mexico (Alcántara & Luna-Vega 2001, Williams-Linera et al 2003. Moreover, the RIV estimates showed that Fagus grandifolia subsp.…”
Section: Discussionsupporting
confidence: 87%
“…The degree of dominance was slightly higher at the La Mojonera site than in the other two forests analyzed, as also noted previously by Godínez-Ibarra et al (2007). In the lower forest layers, the species with highest RIV at all three sites was Magnolia schiedeana, which could be considered as a feature or distinctive characteristic of Mexican beech forests (Peters 1997, Williams-Linera et al 2000, Alcántara & Luna-Vega 2001, Williams-Linera et al 2003, Godínez-Ibarra et al 2007.…”
Section: Discussionmentioning
confidence: 86%
“…The floristic tree composition of the site is similar to that of other fragments of cloud forest in the region (García-Franco, Castillo-Campos, Mehltreter, Martínez, & Vázquez, 2008;López, 2004;Williams-Linera, 2002;Williams-Linera & López, 2008), and also in other states such as Hidalgo (Al- La composición florística arbórea en el sitio es similar a la de otros fragmentos de bosque mesófilo de montaña de la región (García-Franco, Castillo-Campos, Mehltreter, Martínez, & Vázquez, 2008;López, 2004;Williams-Linera, 2002;Williams-Linera & López, 2008), incluso en otros estados como Hidalgo (Alcántara & Luna, 2001;Luna, Alcántara, Ruiz, & Contreras, 2006;Ponce, Luna, Alcántara, & Ruiz, 2006), Tamaulipas (Corral, Aguirre, Jiménez, & Corral, 2005), Jalisco (Santiago, Jardel, & Cuevas, 2003), Chiapas (Escobar & Ochoa, 2007) y Oaxaca (Mejía, Meave, & Ruiz, 2004).…”
Section: Resultados Y Discusiónunclassified
“…Es importante señalar que la abundancia de Q. salicifolia, cuya distribución es ampliamente reportada para la Sierra Madre Occidental (Zavala, 1989), es poco mencionada como dominante en la región, a excepción de este trabajo, el de Haeckel (2006) en Tlalnehuayocan, Veracruz y varias colectas botánicas del estado depositadas en el herbario XALU del Instituto de Ecología, A. C. Lo anterior representa un registro importante y se sustenta en la existencia de afinidades fitogeográficas de la vertiente del Pacífico con la vertiente del Golfo, que se remontan al Pleistoceno (Acosta, 1997;Alcántara & Luna, 2001). …”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation